Assessment of Homogeneity and Convergence of Environmental Performance of Enterprises into One Holding - V. V. Karginova-Gubinova (Финансы: теория и практика)
Taking into account the need for transition to sustainable development of the economy, it seems relevant to consider whether the holding is an effective structure to minimize the negative impact on the environment: is there a convergence of the environmental performance of the holding’s enterprises with a general increase in its responsibility?The purpose of the research is to assess the degree of homogeneity and convergence of the environmental performance of Russian enterprises within the same holding, as well as to determine the relationship between the current level of homogeneity of the holding and the rate of its convergence and overall environmental responsibility. The environmental performance of 11 Russian holdings and 105 constituent enterprises for 2017–2021 was examined.The methodology involved the calculation of entropy and descriptive statistics; the evaluation of the homogeneity of holdings and its convergence, phase transition periods, and the relationship between homogeneity and other characteristics using analysis of variance and regression.The results of the study showed that Russian holdings correspond to the ascending line of the entropic criterion of social development, but at present the phase transition from a heterogeneous to a homogeneous state is incomplete, and homogeneous holdings are unstable. The influence of the type of corporate environmental policy on the homogeneity of the holding, the degree of its convergence and environmental responsibility was revealed.The scientific novelty of the work lies in the consideration of homogeneity and convergence of environmental characteristics of systematically unstudied objects — t he enterprises of one holding; the inappropriateness of the perception of holdings as homogeneous objects is confirmed. Theoretical significance has shown the possibility of using the entropic criterion of the theory of social development and dialectical logic to study the homogeneity and convergence of the indicators of holdings, as well as the developed methodology of their assessment.Recommendations for the authorities and managers of companies, the implementation of which will increase the sustainability of the economy, are of practical value.